Kraft Pulping of Acacia robusta and Acacia mellifera - Bhandari, K. S.; Bhandari, S. S.; Singh, S. V. (Indian Forester, 1983)
Kraft pulps from Acacia rodusta (9 year) and Acacia mellifera (4 year) were produced with 16% Active alkali at 25% sulphidity with pulp yield of 52.23% and 51.16% respectively. The pulps obtained could be bleached with C/E/H/H sequence to a brightness (Elrepho) of 70.62 and 68.0 respectively, the bleached pulp yield being 49.5% and 48.67%, respectively. The bleached kraft pulps obtained from both the species possessed almost similar physical strength properties. The investigations indicate that bleached kraft pulps from Acacia robusta and Acacia mellifera could he used satisfactorily for paper making with the addition of some long fibred pulp.